Severe cutaneous adverse drug reactions: stevens Johnson Syndrom and toxic epidermal necrolysisa, a report of 4 cases seen at UMMC - Khairullah, S.; Ismail, R. (Faculty of Medicine, University of Malaya, 2010)
Prescribing medication is not without its adverse effects. Complications due to drug therapy are on the rise in Malaysia, especially when antibiotics are used indiscriminately. We reviewed cases admitted to the Acute Medical Ward of University of Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia, over a two-month period from March to April 2009. The authors found that Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) were the most common severe adverse cutaneous reactions due to ingestion or parenteral use of drugs. In this report, is a brief description of the two conditions and ways to manage them. The authors have come to a conclusion that judicious use of medications with adequate patient education is important in order to avoid these adverse effects.